(untitled) (Clinics, 2011)
BACKGROUND: High-frequency neuromuscular electrical stimulation increases exercise tolerance in patients with advanced chronic obstructive pulmonary disease (COPD patients). However, it is conceivable that its benefits are more prominent in patients with better-preserved peripheral muscle function and structure. OBJECTIVE: To investigate the effects of high-frequency neuromuscular electrical stimulation in COPD patients with better-preserved peripheral muscle function. Design: Prospective and cross-over study. METHODS: Thirty COPD patients were randomly assigned to either home-based, high-frequency neuromuscular electrical stimulation or sham stimulation for six weeks. The training intensity was adjusted according to each subject's tolerance. Fat-free mass, isometric strength, six-minute walking distance and time to exercise intolerance (Tlim) were assessed. RESULTS: Thirteen (46.4%) patients responded to high-frequency neuromuscular electrical stimulation; that is, they had a post/pre Δ Tlim >10% after stimulation (unimproved after sham stimulation). Responders had a higher baseline fat-free mass and six-minute walking distance than their seventeen (53.6%) non-responding counterparts. Responders trained at higher stimulation intensities; their mean amplitude of stimulation during training was significantly related to their fat-free mass (r = 0.65; p